G259(P) Ensuring Safe Discharges from the Children'S Assessment Unit: Follow-Up of Outstanding Investigation Results. (24th May 2017) - Lythgoe, H; Chan, S; Goldberg, K
Abstract : Aim: Good handover is well recognised as integral to patient safety. NHS England advises a process should be in place for discharged patients to ensure that test results are reviewed promptly. It is recognised that this is not always happening on our Children's Assessment Unit (CAU). Our aim was to audit how many outstanding investigation results we follow up on CAU. We then put in place an intervention and re-audited following introducing the intervention. Methods: We reviewed all patients discharged from CAU from 19th–25th September 2016, determining whether there were any outstanding results by reviewing the day of attendance on the electronic ordering system (Cyberlab). We then reviewed the electronic ward handover (the only system in place at the time). We then implemented a 'CAU outstanding results follow-up book'. This was placed on CAU to provide an easy system to highlight any outstanding results. This book is reviewed daily by the CAU FY1 doctor. We then re-audited between 21st–27th November looking at the electronic handover and the CAU follow-up book to determine if outstanding results were followed up. Our standard was that 100% of outstanding investigation results should be followed up. We compared the pre-intervention and post-intervention results using a Chi-squared test. Results: There were 80 patients in the pre-intervention period and 74 in the post-intervention. 17 patients in the pre-intervention group had outstanding results requiring follow-up, of these 6 were highlighted through the electronic handover (35.3%) compared with 7/18 highlighted in the CAU book (38.9%), in the post-intervention group (p=0.048). This disappointing result may be because we ran this jointly with a more successful initiative to improve the number of discharge letters completed within 24 hours. We promoted this initiative more strongly with significant improvement 15.0% vs 45.9% (p<0.001). This demonstrates change can be achieved. We now plan to present results locally with a drive to improve on the follow-up of outstanding investigations. Conclusions: We have introduced an intervention aiming to improve patient safety through ensuring that all outstanding investigation results are followed-up. So far, results have been disappointing but we hope to improve this with further promotion of the initiative.